1995
DOI: 10.1055/s-0038-1653798
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of C1-Inhibitor as Inhibitor of Tissue-type Plasminogen Activator in Human Plasma

Abstract: SummaryAn enzyme immuno assay was developed to measure complexes of tissue-type plasminogen activator (t-PA) with C1-inhibitor in order to study the role of C1-inhibitor as an inhibitor of t-PA in plasma. In vitro experiments with melanoma and recombinant t-PA learned that purified C1-inhibitor reacts with both single chain t-PA and two chain t-PA. The rate constants ranged from 3.0 to 5.2 M-1s-1 In plasma, melanoma and recombinant two chain t-PA were hardly inhibited by C1-inhibitor, in contrast to melanoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 8 publications
1
20
1
3
Order By: Relevance
“…The tPA/C1 inhibitor concentrations measured in this investigation are slightly higher than those in an earlier study on a small number of individuals [12]. This might, at least partially, be due to a standardization problem.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The tPA/C1 inhibitor concentrations measured in this investigation are slightly higher than those in an earlier study on a small number of individuals [12]. This might, at least partially, be due to a standardization problem.…”
Section: Discussioncontrasting
confidence: 83%
“…These compounds, in addition to free tPA and tPA in complex with a 2 -macroglobulin [9,12] constitute tPA antigen in plasma. The latter two compounds have functional tPA activity, while tPA in complex with PAI-1, antiplasmin and C1 inhibitor are inactive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate extraction fractions were used for each factor measured. Huisman et al [41] reported a half-life of 4.2 min for the clearance of t-PA/C1-I complex [41]. The hepatic extraction fraction for t-PA/C1-I was adjusted to produce a halflife of 4.2 min in the simulation.…”
Section: The Fibrinolytic Modelmentioning
confidence: 99%
“…C1 inhibitor has also been implicated in regulating the formation of the C4C2 complex via the lectin pathway by inactivating mannan-binding, lectin-associated proteases 1 and 2 (12,13). Similarly, inhibitory effects on tissue plasminogen activator and plasmin (with a consequent increased breakdown of the fibrin clot) have been described, although these are thought to play only a minor role (14). Despite the regulatory role C1-INH plays in the previous pathways, most authorities believe that C1-INH's function of inhibiting the conversion of prekallikrein to kallikrein is the major pathophysiologic event resulting in angioedema in HAE patients.…”
Section: Pathophysiologymentioning
confidence: 99%